2008
DOI: 10.1542/peds.2007-2392
|View full text |Cite
|
Sign up to set email alerts
|

Bone Metabolism in Adolescent Athletes With Amenorrhea, Athletes With Eumenorrhea, and Control Subjects

Abstract: OBJECTIVE-We hypothesized that, despite increased activity, bone density would be low in athletes with amenorrhea, compared with athletes with eumenorrhea and control subjects, because of associated hypogonadism and would be associated with a decrease in bone formation and increases in bone-resorption markers.METHODS-In a cross-sectional study, we examined bone-density measures (spine, hip, and whole body) and body composition by using dual-energy radiograph absorptiometry and assessed fasting levels of insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
117
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(134 citation statements)
references
References 56 publications
(58 reference statements)
10
117
1
6
Order By: Relevance
“…Previous studies have reported lower lumbar spine BMD in amenorrheic than eumenorrheic athletes (13,(34)(35)(36).…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have reported lower lumbar spine BMD in amenorrheic than eumenorrheic athletes (13,(34)(35)(36).…”
Section: Discussionmentioning
confidence: 93%
“…In fact, doubling the radius of the bone increases bone strength by a factor of 16 [34]. As such, a smaller femoral neck CSA and CSMI among female athletes with past and/or current menstrual disturbances when compared with athletes who have always had regular menstrual cycles may be detrimental to bone health by compromising bone strength and by adding to the negative effects that low BMD [4,11,12,15] has on bone strength. Interestingly, the C/P-RIR group demonstrated the smallest proportion of women with low neck diameter compared with both the C + P-IR group and the C + P-R group, which had similar proportions of women with low-neck diameter.…”
Section: Discussionmentioning
confidence: 99%
“…high as 60% [11], and the co-existence of menstrual irregularity and compromised BMD has been repeatedly observed [4,5,[12][13][14][15]. Functional hypothalamic amenorrhea, defined as the absence of menses for greater than 90 days (secondary amenorrhea) [16] or the failure to attain menarche by age 15 (primary amenorrhea) [17] which cannot be explained by other underlying pathology [17], and oligomenorrhea, defined as irregular and inconsistent menses at intervals of 36 to 90 days [16], are the most severe presentations of menstrual cycle disturbances and are linked to poor skeletal health [3,5,8].…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…When female athletes become amenorrheic, the protective effect of exercise on BMD is lost. 65 Children who are immobilized have rapid declines in bone mass.…”
Section: Exercise and Lifestylementioning
confidence: 99%